The manipulative disguise of truth tricks and threats of implicit communication - Masia, Viviana (Pragmatics & beyond new series,, 2021)
"Becoming effective hunters of manipulative communicative moves is far from an easy capacity to develop. This book aims at offering a guide to the most dangerous traps of deceptive language as triggered by implicit communication strategies such as presupposition, implicature, topicalization and vague expressions. A look at different contexts of language use highlights some of the most remarkable implications of using indirect speech and of how it affects the correct comprehension of a message. Within the remit of communication and pragmatics studies, this work marks an advancement in the direction of delving into the linguistic manifestations of manipulative discourse, its most common contexts of use and the educational paths that can be undertaken to master it in everyday interactions"--